Molecular studies of rust on European aspen suggest an autochthonous relationship shaped by genotype - Siddique, Abu Bakar; Menke, Laura; Dinedurga, Melis; Albrectsen, Benedicte Riber (Frontiers in Plant Science, 2023)
Forests are at increasing risk from pathogen outbreak. Climate change for example enhance the risk of local disease outbreaks, and naturalization of exotic pathogens may follow human activities, warranting robust pest surveillance routines to support forest management. Melampsora pinitorqua (pine twisting rust) is of concern in Swedish forestry, and here we evaluate the use of visible rust scores (VRS) on its obligate summer host, European aspen (Populus tremula) as a tool for quantification of the pathogen. With use of species-specific primers, we could detect the native rust, but we failed to detect two exotic rusts (M. medusae and M. larici-populina). We found that aspen genotype determined the presence of fungal genetic markers (amplifying the ITS2 region of the fungal rDNA sequence) as well as DNA sequences specific to M. pinitorqua. We correlated VRS with the amount of fungal DNA in the same leaf, and we related the findings to aspen genotype-specific parameters such as the ability to synthesize and store leaf condensed tannins (CT). At the genotype level both positive and negative relationships were observed between CTs, fungal markers, and rust infestations. However, at the population level, foliar CT concentrations correlated negatively with general fungal- and rust-specific marker abundances. Our results, therefore, do not support the use of VRS to assess Melampsora infestation in Aspen. They do, however, suggest that the relationship between European aspen and rust infestation may be characterized as autochthonous in northern Sweden.